Does Setting Matter? An Exploratory Examination of Victimization Risk Reduction Strategies Among Female College Students Studying Abroad - Tamborra, Tracy L. (Violence against women, 2022)
This exploratory project assessed whether female college students studying abroad engage in more risk reduction strategies (RRSs) when abroad than in their community of origin and whether changes in students' use of RRSs while abroad are related to a variety of factors (e.g., fear of victimization, year of study). Results revealed that students engaged in significantly more RRSs while abroad and that students studying in Africa were more likely to increase their use of RRSs. Seniors engaged in fewer RRSs. Results extend the RRS literature by confirming that the employment of strategies is location dependent and associated with other factors.